2017
DOI: 10.1002/bmb.21039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge of participants on basic molecular biology techniques after 5‐day intensive molecular biology training workshops in Nigeria

Abstract: The deployment of molecular biology techniques for diagnosis and research in Nigeria is faced with a number of challenges, including the cost of equipment and reagents coupled with the dearth of personnel skilled in the procedures and handling of equipment. Short molecular biology training workshops were conducted at the Nigerian Institute of Medical Research (NIMR), to improve the knowledge and skills of laboratory personnel and academics in health, research, and educational facilities. Five-day molecular bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…covering biotechnology topics have been reported to improve technical skills as well as knowledge of the subject [60]. Yisau, et al [61], reported that the combination of theoretical courses with applied laboratory sessions significantly increased the knowledge and skills of participants in molecular biology in a five-day intensive molecular biology training workshop.…”
Section: Discussionmentioning
confidence: 99%
“…covering biotechnology topics have been reported to improve technical skills as well as knowledge of the subject [60]. Yisau, et al [61], reported that the combination of theoretical courses with applied laboratory sessions significantly increased the knowledge and skills of participants in molecular biology in a five-day intensive molecular biology training workshop.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, the report noted that biology instruction has not changed substantially since the 1980's, even although science has changed at a rapid pace . Innovations in classroom approaches have occurred in the past decade , necessitating development of assessment tools to see if these changes have simply been made for change's sake or if they are resulting in significant increases in student learning. The NRC recently looked at the development of concept inventories and expressed a need for more specific instruments addressing biology concepts .…”
Section: Introductionmentioning
confidence: 99%